The Metrical Parameters of Word Stress Production and Perception among Iraqi English as a Foreign Language (EFL) Learners (KEMANUSIAAN The Asian Journal of Humanities, 2016)
This paper disscusses the impact of glocalisation process on the production and perception of Iraqi English as a foreign language (EFL) learners in word stress placement pertaining to metrical parameters. Previous studies lack an in-depth investigation of the parameters tracing the prosodic acquisition path of the learners in acquiring L2 (Archibald 1993; Youssef and Mazurkewich 1998). This study which adopts the metrical parameters model of Dresher and Kaye (1990) shows how similar metrical parameters settings of both Arabic and English affect the performance of Iraqi EFL learners in word stress placement. The findings of the study reveal how Iraqi learners of English internalise the conceptualisation of the metrical parameters of English word stress production and perception in their glocalised variety of English as part of learning the language as an international (global) language. The findings of the study also suggest that Iraqi EFL learners assigned more incorrect responses in word stress placement in the perception task than the production task because they followed different parameter-setting orders in acquiring L2, leading to them resetting more parameters wrongly in the perception task than the production task. The study highlights on the importance of accepting both global and local varieties of English in curriculum development in Iraq.